Problems of introducing the betterment levy - Nowakowska, Oliwia; Pęska-Siwik, Agnieszka; Maciuk, Kamil (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
Every individual expects their state to ensure internal security and promote both economic and social development, providing better living standards and access to material goods while striving to reach the social standard of living of other countries. The state treasury and local government units are responsible for the development and modernisation of municipalities. Municipalities deliver various social and economic goods to their residents by performing numerous tasks and activities that require monetary outlay, all while improving quality of life. In light of this, decisions are made to adopt resolutions aimed at obtaining public funds for further development. One way for municipalities to secure additional public funds for public purposes is by introducing a resolution for a betterment levy, which addresses the increase in real estate value following subdivision. Allowing municipalities to benefit from the increase in real estate value caused by its division can create a significant financial base for them. This paper attempts to present the functioning of the betterment levy institution regarding real estate division, along with statistical data on its occurrence. To this end, information obtained during research in six districts of the Świętokrzyskie Voivodeship, encompassing a total of fifty communes, was compiled. The research primarily involved determining the number of municipalities that adopted a resolution on the betterment levy, identifying the percentage rate of the levy they adopted, and examining the number of issued decisions regarding the imposition of the betterment levy over a five-year period (2015-2019) in the Świętokrzyskie Voivodeship.